To solve the expression \( 15 \cdot 8^0 / 5 + 4(7^0 - 6) \), we will start by evaluating the powers and then simplify.
-
Calculate \( 8^0 \) and \( 7^0 \).
- For any non-zero number, the power of zero is 1, so: \[ 8^0 = 1 \quad \text{and} \quad 7^0 = 1 \]
-
Substitute these values back into the expression: \[ 15 \cdot 1 / 5 + 4(1 - 6) \]
-
Calculate \( 15 \cdot 1 / 5 \): \[ 15 / 5 = 3 \]
-
Now calculate \( 4(1 - 6) \): \[ 1 - 6 = -5 \] Therefore: \[ 4(-5) = -20 \]
-
Combine the two results: \[ 3 - 20 = -17 \]
The final result of the expression \( 15 \cdot 8^0 / 5 + 4(7^0 - 6) \) is: \[ \boxed{-17} \]